2013
DOI: 10.3109/00365513.2013.841985
|View full text |Cite
|
Sign up to set email alerts
|

Analytical performance, agreement and user-friendliness of five C-reactive protein point-of-care tests

Abstract: Analytical performance, agreement, and user-friendliness of the POC CRP tests varied considerably, yet overall four devices showed adequate analytical performance and agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…However, we did not manually correct for Ht, as this is in general not possible in POC situations. Several POC CRP analyzers have already been evaluated by others [4][5][6][7][8][9][10] but all except one [10] in a one to one comparison with a central laboratory method. The correlation coefficients are in general N0.95 comparable with our findings.…”
Section: Evaluation Of the Quantitative Crp Analyzersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not manually correct for Ht, as this is in general not possible in POC situations. Several POC CRP analyzers have already been evaluated by others [4][5][6][7][8][9][10] but all except one [10] in a one to one comparison with a central laboratory method. The correlation coefficients are in general N0.95 comparable with our findings.…”
Section: Evaluation Of the Quantitative Crp Analyzersmentioning
confidence: 99%
“…In one method the measurement of the white blood cell count is combined with that of CRP [9]. In all those studies except one [10] just one method or apparatus has been evaluated and compared with an automated routine method. In this study we investigated the various commercially available methods on their applicability for general practice.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when compared to the Beckman Coulter analyser, the i-CHROMA™ CRP method showed a good correlation (r 2 =0.84) and as a result was recommended as an attractive instrument for medical centers [12]. Minnard et al also showed in two comparative studies comparing the i-CHROMA™ method with some common CRP POCTs that the i-CHROMA™ CRP method is a good method for measuring CRP values [13,14]. One study by Brouwer et al also confirmed the i-CHROMA™ CRP method a good CRP POC test [15].…”
Section: Discussionmentioning
confidence: 99%
“…The CRP POCT instrument that is used in this study (QuikRead go®, Orion Diagnostica Oy) has been shown to have adequate analytical accuracy and agreement with laboratory measurements [43,44]. The analyzer has a built-in self-check procedure that secures its correct use and correct results.…”
Section: Technical Features Of Crp Poctmentioning
confidence: 99%